Building the semiotic meaning of critical thinking from the Prophet Ibrahim's discourses in the scene of da'wah to his father in the Qur'anic story - Mhd Ramli, Mhd Faizal; Othman, Mohd Sukki; Hajimaming, Pabiyah; Wan Sulong, Wan Muhammad (Universiti Sains Islam Malaysia (USIM), 2023)
This research aims to build the semiotic meaning of critical thinking from Prophet Ibrahim's discourses in the scene of dawah to his father, which were part of the scenes of the Qur'anic story. Although the study of critical thinking is of interest to researchers in the field of contemporary education, many people still neglect and ignore the logical and rational aspects of Prophet Ibrahim's discourses as a comprehensive scientific approach to critical thinking based on divine revelation.This has led to Muslims being accused of stagnation and backwardness due to their inability to provide evidence and produce new knowledge from the Holy Quran in line with the development of contemporary knowledge.The research adopted the descriptive analytical approach through the semiotic pragmatic method pioneered by Peirce, which consists of components namelyrepresentamen, object and interpretant, and the research relied on thecritical thinking elements by the Delphi Report, as the basis for this research. The result concluded that there are three elements of critical thinkingbehind the sign of Prophet Ibrahim's discourses in the scene of dawah to his father;interpretation, self-regulation, and evaluation. The most important indications drawn by the researchers is that apreacher or ateacher must use various methods and means in his teachingto achieve his goal.Emotional and rational aspects are the two most important components in educating people. Therefore, the aspect of love in teaching and education should be considered to suit the needs and suitability of situations.